Genetic analysis of resistance to flower bud thrips (Megalurothrips sjostedti) in cowpea (Vigna unguiculata [L.] Walp.) - Omo-Ikerodah, E.E.; Fatokun, C.A.; Fawole, I. (2009)
Cowpea is an important legume in sub-Saharan Africa where its protein rich grains are consumed. Insect pests constitute a major constraint to cowpea production. Flower bud thrips (FTh) is thefirst major pest of cowpea at the reproductive stage and if not controlled with insecticides is capable of reducing grain yield significantly. Information on the inheritance of resistance to FTh is required to facilitate breeding of resistant cultivars. The genetics of resistance was studied in crosses of four cowpea lines. Maternal effect was implicated while frequency distributions of the F2 and backcross generations suggest quantitative inheritance. Additive, dominance and epistatic gene effects made large contributions and since improved inbred lines are the desired product, selection should not be too severe in the early generations to allow for desirable gene recom-bination. This study suggested that some of the genes involved in the control of resistance to FTh are different in TVu1509 and Sanzi. Broad sense heritability ranged from 56% to 73%. Choice of maternal parent in a cross will be critical to the success of resistance breeding.